Truss-like structure design with local geometry control. Issue 3 (16th April 2017) - Liu, Jikai; Ma, Yongsheng
Abstract : This paper presents a local geometry control method when designing truss-like structures. Two kinds of local geometry measures are proposed: the local grid area and the local grid incircle radius. Both measures work effectively in constraining the local geometry and the selection is problem-dependent. To prove the effectiveness of the local geometry control, two shape optimization examples are studied by optimizing the nodal design freedoms. For topology optimization, the ground structure problem plus nodal design freedoms are employed and the simultaneous optimization approach is adopted to solve the optimization problem. It is highlighted that the local geometry constraints are dynamically applied to varying objects because of the grid merging caused by truss element elimination. The dynamic constraints would cause local fluctuation during the optimization process but would not impact the overall convergence. GRAPHICAL ABSTRACT: